Problems of ensuring the security of an individual’s economic trace on the Internet - Krasilnikov, Oleg Yu. (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право», 2022)
Introduction.The article deals with the problems of ensuring the security of economic information of individuals on the Internet. The concept and forms of the economic Internet trace of the individual are investigated. Theoretical analysis. Fraudulent actions in a virtual environment directed against individuals account for a signifi cant proportion of the total number of cybercrimes. The main motive of the off enses is to obtain fi nancial benefi ts, and the method is the distribution and use of malicious software. The contradiction between formal institutions of economic cybersecurity and informal institutions of virtual fraud is analyzed, and the ways of its resolution are presented: tightening control and organization of harmonious interaction of economic agents. The forms of institutional coordination of subjects on the basis of market relations are investigated: the introduction of a cooling-off period during fi nancial transactions; the determination of the minimum amount of funds after which the transaction is subject to mandatory control by fi nancial structures and supervisory authorities; the establishment of the amount of funds that banks must return in a simplifi ed and unconditional manner to customers – individuals who have become victims of cybercriminals; the introduction of blockchain technology. Special attention is paid to the formation of fi nancial literacy of the population. The author notes an increase in cases of cyberbullying during the coronavirus pandemic. Results. The conclusion is made about the weakness of state and market institutions to protect the economic Internet trace of the individual. It is proposed to develop an appropriate state strategy to improve the security of the individuals’ economic information use on the Internet.